Evaluasi Keamanan Teknologi Informasi Menggunakan Indeks Keamanan Informasi 5.0 dan ISO/EIC 27001:2022 - Jelita, Lucia Devlina Adventia; Al Azam, Moh Noor; Nugroho, Aryo (STMIK Palangkaraya, 2024)
In the era of digital transformation, data has become something valuable but vulnerable to leaks. According to Lanskap Keamanan SIber Indonesia 2022, there were 311 data leakage incidents that occurred in Indonesia. Many tools can be used to evaluate information security, one of which is the Information Security Index (ISI). KAMI is a tool to assess the level of information security readiness of an organization based on the SNI ISO / IEC 27001 standard. PT Kano Teknologi Utama is a company that uses information technology in its daily operations. Therefore, researchers conducted an information technology security evaluation to determine the condition of information security and can evaluate it so that security becomes better. The evaluation is carried out by conducting observations and interviews at the company. The data that has been obtained will then be assessed according to OUR Index. Based on the results of the Our Index assessment, the electronic system category score obtained is 19 and is included in the high category. While the final evaluation result is